2019
DOI: 10.1109/tbme.2018.2878555
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic Properties of Human Autopsy Brain Tissues as Biomarkers for Alzheimer's Diseases

Abstract: Objective: The present study investigates viscoelastic properties of human autopsy brain tissue via nanoindentation to find feasible biomarkers for Alzheimer's Disease (AD) in ex vivo condition and to understand the mechanics of the human brain better, especially on the difference before and after progression of AD.Methods: Viscoelastic properties of paraformaldehyde-fixed, paraffin-embedded thin (8 μm) sectioned normal and AD affected human autopsy brain tissue samples are investigated via nanoindentation wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 57 publications
0
27
0
Order By: Relevance
“…These results also support some investigations conducted at the tissue level; a study that used microindentation on freshly resected, human brain tissue also reported that WM was stiffer than cortical GM when evaluated with various strain rates and relaxation function parameters (Finan, Sundaresh, Elkin, McKhann, & Morrison, 2017). Mechanical indentation tests have also revealed that GM is approximately one third softer than WM in the porcine (Kaster, Sack, & Samani, 2011; van Dommelen, van der Sande, Hrapko, & Peters, 2010) and bovine brain (Budday et al, 2015), although other studies from the microindentation literature have shown the opposite trend (Budday et al, 2017; Park, Lonsberry, Gearing, Levey, & Desai, 2019). The discrepancy is possibly due to investigations being performed at the microscale returning mechanical properties that differ from the macroscale properties measured with MRE.…”
Section: Discussionmentioning
confidence: 99%
“…These results also support some investigations conducted at the tissue level; a study that used microindentation on freshly resected, human brain tissue also reported that WM was stiffer than cortical GM when evaluated with various strain rates and relaxation function parameters (Finan, Sundaresh, Elkin, McKhann, & Morrison, 2017). Mechanical indentation tests have also revealed that GM is approximately one third softer than WM in the porcine (Kaster, Sack, & Samani, 2011; van Dommelen, van der Sande, Hrapko, & Peters, 2010) and bovine brain (Budday et al, 2015), although other studies from the microindentation literature have shown the opposite trend (Budday et al, 2017; Park, Lonsberry, Gearing, Levey, & Desai, 2019). The discrepancy is possibly due to investigations being performed at the microscale returning mechanical properties that differ from the macroscale properties measured with MRE.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it has increasingly been recognized that mechanical signals play an important role for brain development (Budday et al, 2015b;Koser et al, 2016;Thompson et al, 2019), injury (Meaney et al, 2014;Hemphill et al, 2015;Keating and Cullen, 2021), and disease (Murphy et al, 2016;Barnes et al, 2017;Gerischer et al, 2018;Park et al, 2018). In silico modeling based on the theory of nonlinear continuum mechanics has therefore proven a valuable tool to, on the one hand, computationally test hypotheses that complement experimental studies and provide a predictive understanding of processes in the brain under physiological and pathological conditions (Goriely et al, 2015;Budday et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The chronic neuroinflammation causes disease-related symptoms, such as loss of neurons and synapses ultimately leading to memory problems and dementia [13]. In addition to the underlying biological processes in AD, the investigation of mechanical properties received attention in recent years as a potential biomarker for early diagnosis, as shown by magnetic resonance elastography (MRE) studies where brain elasticity and viscosity decreased in AD human patients [14,15,16,17,18,19], and as a novel drug target for tissue regeneration [? 20].…”
Section: Introductionmentioning
confidence: 99%